Good news, bad opinions: press coverage about ChatGPT in Portugal - Essenfelder, Renato (2024)
This paper analyzes 53 articles published in the Portuguese newspapers Público and Expresso about ChatGPT. The articles were categorized into opinion pieces and informative articles, and content analysis, sentiment analysis and a general polarity classification (positive, negative, or neutral) were applied to the texts. The results indicate a correlation between opinion pieces and feelings of anger and fear, suggesting that while news reporting views the phenomenon of generative artificial intelligence as either positive or neutral, commentators in these newspapers are hesitant towards the technology.